PROPONENTS AND OPPONENTS OF BILINGUALISM (مجلة ديالى للبحوث الانسانية, 2022)
PROPONENTS AND OPPONENTS OF BILINGUALISM Bilingualism is a multi-faceted phenomenon, opening to a variety of descriptions, interpretations and definitions. It may be tinged with bias, and it frequently carries either positive or negative connotations.                                                                                            So, it is not an easy task to describe and delimit this phenomenon to those who are unaware of the notion of bilingualism and their individual bilinguality. Many people in general and students in particular who are not specialized in English language and linguistics do not know what is meant by the term ‘bilingualism’ ;whether they can be called bilinguals of not; and what are the necessary demands and factors for being proficient bilinguals.           This paper regards bilingualism as one of the most important aspects in worldwide communication. Therefore, each bilingual has to be conscious of his/her bilinguality in order to possess self-confidence during the use of the two languages.        This paper aims at bringing forth part of the phenomenon of bilingualism to those who are acquiring a new language. It also aims at pointing out how important to understand the real nature of this phenomenon in helping bilinguals to overcome many obstacles they might face during the acquisition of a new language and to improve their newly- acquired language by the aim this newly acquired language fulfils.